ZERO : Vision und Bewegung : Werke aus der Sammlung Lenz Schönberg. - Zweite, Armin; Weitemeier, Hannah (München : Städtische Galerie im Lenbachhaus, 1988)
Arman ; Aubertin, Bernard ; Bartels, Hermann ; Bonalumi, Agostino ; Bostik, Vaclav ; Bury, Pol ; Castellani, Enrico ; Colombo, Gianni ; Dzamonja, Dusan ; Dorazio, Piero ; Fontana, Lucio ; Girke, Raimund ; Goepfert, Hermann ; Gonschior, Kuno ; von Graevenitz, Gerhard ; Graubner, Gotthard ; Hiltmann, Jochen ; von Hoeydonck, Paul ; Holweck, Oskar ; etc.
Vision und Bewegung - ZERO : Werke aus der Sammlung Lenz Schönberg, Städtische Galerie im Lenbachhaus, München, 28.9. - 6.11.1988
boek